Conflict, Household Victimization, and Welfare : Does the Perpetrator Matter? - Kaila, Heidi; Azad, M. Abul Kalam (World Bank, Washington, DC, 2019)
This paper studies the relationship between conflict and household welfare by using a detailed panel data set of household victimization across the most conflict-affected regions in Nigeria between 2010 and 2017, during a time characterized by a sharp increase in conflict. The North East region has been hardest hit with the recent Boko Haram insurgency. The North Central region has seen clashes between herders and farmers over land and resources. Several militant groups operate in the oil-producing Niger Delta region, where their aim is to extract resources by disrupting oil production. By exploiting the plausibly exogenous variation in the timing, intensity, and spatial distribution of victimization, this study finds that becoming a victim of conflict leads to higher food insecurity and decreased consumption. Since different types of actors have different motivations for their actions, the consequences of victimization might vary depending on the perpetrator. The study finds that events perpetrated by insurgents are the most detrimental to consumption, whereas food insecurity increases as a consequence of insurgent and criminal activity. This is in line with the results being strongest in the North East, which also has the highest intensity of conflict. The study also finds that property-related events are more detrimental to consumption and food insecurity than are violent events. Likewise, it finds suggestive evidence that violent events, as well as events perpetrated by insurgents and bandits, are detrimental to mental health. The findings highlight the importance of collecting nuanced information on victimization in conflict-affected areas.